Realisasi Perjanjian Perdamaian DOHA Dialogue antara Afaghanistan-Amerika Serikat dan Taliban Periode Kepemimpinan Ashraf Ghani - Zhafir, Ali Zhafir Talmullah (Universitas Sulawesi Barat, 2022)
The long conflict that occurred in Afghanistan resulted in many casualties and setbacks in the field of peace. The events that took place on the land were the aftermath of foreign occupations under the pretext of promoting the progress and prosperity of the Afghan state. The difference in peaceful views between the United States and the Afghan government is different from the Taliban, so the three parties do not stop carrying out attacks. The United States and the Government of Afghanistan consider that the definition of peace is a situation in which extremist groups including the Taliban no longer exist in Afghanistan, while the Taliban considers that peace can be achieved if Afghanistan can stand alone without any intervention from foreign countries. As a result, the peace process is often hampered due to the strong differences between the parties. The author will use the concepts of conflict resolution and cooperation to analyze the peace process in Afghanistan. Descriptive qualitative research method is used to explore more deeply how the realization of the doha agreement is implemented. It is the urgency of humanity that makes the author interested in discussing research on the Doha agreement. Keywords : conflict, doha agreement, united states of america, government of afghanistan, taliban.